2017
DOI: 10.1016/j.bjm.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

New production process of the antifungal chaetoglobosin A using cornstalks

Abstract: Chaetoglobosin A is an antibacterial compound produced by Chaetomium globosum, with potential application as a biopesticide and cancer treatment drug. The aim of this study was to evaluate the feasibility of utilizing cornstalks to produce chaetoglobosin A by C. globosum W7 in solid-batch fermentation and to determine an optimal method for purification of the products. The output of chaetoglobosin A from the cornstalks was 0.34 mg/g, and its content in the crude extract was 4.80%. Purification conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Chaetoglobosins are a class of mycotoxins with both antifungal and anticancer activities ( ALi et al. 2015 ; Jiang et al. 2017 ) found in the distantly related Chaetomium globosum (Sordariomycetes) and some Eurotiomycetes ( Schümann and Hertweck 2007 ) ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chaetoglobosins are a class of mycotoxins with both antifungal and anticancer activities ( ALi et al. 2015 ; Jiang et al. 2017 ) found in the distantly related Chaetomium globosum (Sordariomycetes) and some Eurotiomycetes ( Schümann and Hertweck 2007 ) ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that such core microbiomes have a variety of potential beneficial effects in maintaining soil health and plant growth, such as antibiotic production, heterologous material degradation, heavy metal adsorption, and root colonization ( 35 , 40 , 41 ). Chaetomium produces cellulase and chaetomin, which can inhibit pathogenic fungi growth and promote the activation of soil nutrients ( 42 , 43 ). Penicillium can degrade harmful substances in soil, and its secondary metabolites can significantly inhibit some pathogens ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, C. globosum was grown in 50‐ml PDB and shaken at 28°C for 8 days. Then, the liquid culture was extracted with an equal volume of acetone [21]. Furthermore, the organic phase was concentrated by a vacuum evaporator until dry, under reduced pressure at 55°C.…”
Section: Methodsmentioning
confidence: 99%